2015
DOI: 10.5539/gjhs.v8n2p9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness and Self-Care Practices of Hypertension Among Cardiac Hypertensive Patients

Abstract: Introduction:The most prevalent form of hypertension is systolic blood pressure (SBP) and it is considered to be predisposing risk factor for cardiovascular disease. The objective of the study was to assess self-care practices, knowledge and awareness of hypertension, especially related to SBP among cardiac hypertensive patients.Methodology:A Cross sectional study was conducted on 664 cardiac hypertensive patients, which were selected by non-probability convenience sampling from cardiology outpatient departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
29
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 18 publications
(18 reference statements)
10
29
2
Order By: Relevance
“…This finding is consistent with the studies conducted in Addis Ababa (23%) [20] and Nigeria (16.4%) [19]. However, this finding is lower than the study conducted in south Ethiopia (27.3%) [21] and India (37.1%) [25]. This could be explained by socio-cultural variation that influences life style of individuals, sample size difference and variation in the components of self-care practice assessment tool.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with the studies conducted in Addis Ababa (23%) [20] and Nigeria (16.4%) [19]. However, this finding is lower than the study conducted in south Ethiopia (27.3%) [21] and India (37.1%) [25]. This could be explained by socio-cultural variation that influences life style of individuals, sample size difference and variation in the components of self-care practice assessment tool.…”
Section: Discussionsupporting
confidence: 90%
“…Respondents < 65 years old had 3.26 [AOR = 3.26, CI 95, 1.03–10.35, p = 0.044] more good self-care practice than ≥ 65 years old respondents. This finding was in line with the study conducted in India which showed older age is associated with unfavorable self-care practice [25]. This was supported by the study conducted in South Ethiopia which showed patients aged ≥ 65 years were less likely to have good lifestyle modification practice than patients with < 65 years [21].…”
Section: Discussionsupporting
confidence: 87%
“…A similar observation was made in a study conducted in Debra Berhan in Ethiopia, 26 but this finding disagrees with the study conducted in Addis Ababa, Ethiopia. 29 This difference is due to the differences in access to media 28,39,40,51 and can have better access to healthcare services than those living in small towns. 25,31,51 In this study, having adequate knowledge about hypertension improves self-care practice.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, from the study conducted in Pakistan, about twothirds of them (69.1%) had regular checkup of their blood pressure status. 34 The study has certain limitations such as; retrospective cross-sectional study design, single centered, and small sample size used.…”
Section: Dovepressmentioning
confidence: 99%